Evaluating the impact of a new educational tool on understanding of polygenic risk scores for alcohol use disorder - Driver, Morgan N.; Kuo, Sally I-Chun; Petronio, Lia; Brockman, Deanna; Dron, Jacqueline S.; Austin, Jehannine; Dick, Danielle M. (Frontiers in Psychiatry, 2022)
As gene identification efforts have advanced in psychiatry, so have aspirations to use genome-wide polygenic information for prevention and intervention. Although polygenic risk scores (PRS) for substance use and psychiatric outcomes are not yet available in clinical settings, individuals can access their PRS through online direct-to-consumer resources. One of these widely used websites reports that alcohol use disorder is the third most requested PRS out of >1000 conditions. However, data indicate that there are misunderstandings about complex genetic concepts, with a lower understanding of PRS being associated with a more negative impact of receiving polygenic risk information. There is a need to develop and evaluate educational tools to increase understanding of PRS. We conducted a randomized controlled trial to evaluate the impact of web-based educational information on understanding of PRS for alcohol use disorder. 325 college students (70.4% female; 43.6% White; mean age = 18.9 years) from an urban, diverse university completed the study. Overall, participants were highly satisfied with the educational information. Results from a one-way ANOVA indicated that there was a significant increase in overall understanding of PRS for alcohol use disorder (p value < .001), among individuals who received educational information about PRS and alcohol use disorder, as compared to receiving no accompanying information (adj. p value < .001), or educational information about alcohol use disorder only (adj. p value < .001). These findings suggest that the web-based educational tool could be provided alongside polygenic risk information in order to enhance understanding and interpretation of the information. The study was registered on ClinicalTrials.gov (Identifier: NCT05143073).